Rancang Bangun Aplikasi Pengadaan Barang dan Jasa Universitas Negeri XYZ dengan Metode Extreme Programming - Muhammad Galih Wonoseto; Arman Maulana; Mahfud Asyari (UIN Sunan Kalijaga Yogyakarta, 2023)
The Indonesian government has provided the LKPP application in procuring goods and services for government agencies. However, several procurement processes at XYZ State University still do not use the LKPP application. Some of the reasons that are often stated are that the goods available in LKPP are not complete and the location of suppliers in LKPP is outside the city and the province. It is required to create an application for them at XYZ State University to promote digitization and transparency in procuring products and services at XYZ University. This application development uses the extreme programming method. This research succeeded in identifying the functionality requirements required in e-purchasing applications. The results of this research were able to realize 91.6% of all the necessary features. Some features that can be recognized include dashboard features, user access rights sharing features, goods/services requirements features, goods/services offering features, goods/services offer approval features, payment features, and specification features. The feature that has not been fulfilled is the direct purchase feature. The applications produced in this research may be adapted at universities or other government agencies.